Drug safety management in the operation room of referral hospital: cross-sectional study. (2020) - Workie, Misganaw Mengie; Chekol, Wubie Birlie; Fentie, Demeke Yilkal; Bizuneh, Yosef Belay; Ahmed, Seid Adem
Abstract: Background: Medication administration safety should always be at the forefront of anesthesia practices. The incorrect preparation, labeling and injection of wrong medications are some of medication errors occurring in the operation theatres. This audit was aimed to determine whether operation room drug safety management in our theatre meet the audit standards or not. Methods: This audit was conducted from November 20 to 27; 2019. All surgical procedures done in Main Operation Rooms of Referral Hospital were included. Data were collected by direct observation using standardized checklist prepared from recommendations of Australian and New Zealand College of Anesthetists (ANZCA) and British Journal of Anesthesia (BJA) guidelines. Data were collected prospectively before, during and after operation. Results: Total of 50 surgical procedures were observed of their drug safety management before, during and after operation. From those audit standards, only labeling of the injectable drugs was fully practiced. However, swabbing of vial tops to minimize infection rate, formal organization of drug drawers and drug administration time recording were not practiced at all. Conclusions: Level of drug safety management in our operation theatre was unsatisfactory. So, added vigilance is needed in standards that scored below the average and those audit standards that were not practiced at all. Highlights: Medication administration safety should always be at the forefront of anesthesia practices. Level of drug safety management in our operation theatre was unsatisfactory. Organization of drug drawers and drug administration time recording were not practiced at all. Added vigilance is needed in standards that scored below the average of standards.